The Correspondece of Kazimieras Barėnas in the Dr. K. Pemkus Library at the Archive of the Klaipėda University Library - Steponavičiūtė, Emilija Danutė (Bibliotheca Lituana, 2018)
[full article and abstract in Lithuanian; summary in English] Klaipėda University Library holds a collection that it had received as a gift by Kazys Pemkus (1920–1996) – bibliophile, doctor and notable person in exile. This collection contains not only a set of valuable books and periodicals, which counts more than 64 000 copies of already processed publications, but various documents connected to many famous Lithuanians in exile: reports of their activity, drafts of their writings, notes, correspondence, photos etc. Comparing with other personal archives preserving in this collection, there is not a very big number of Kazimieras Barėnas’ egodocuments. There are 26 of his letters that are discussed in this article for the first time. The chronology of K. Barėnas (1907–2006) letters embrace the period from August 8, 1948 to January 24, 1975. The letters analyzed in this article help us discover K. Barėnas not only as a journalist, publisher and editor, but the perspective that this person had on matters regarding the Lithuanian language, books, emigration and writing as well. The analyzed letters acquaint the reader with two Lithuanian writers, native from Aukštaitija: Alfonsas Šešplaukis-Tyruolis (1909–2006) and Juozas Švaistas (1891–1978) and the history of the publication of their writings. There is some focus on the literary yearbook Pradalgės, published in London during 1964–1980; its publication history, the seeking for writers and collaborations are described in the article. In writing on organizational matters and answering various requests, K. Barėnas inserts his insights on exile and writing. Respectfully, with tact but together with gentle humor, he communicates with the writers. In reading those letters, one can feel the big workload, the lack of time and, in the latest letters, some reminders about tiredness. Despite the moderate amount of the analyzed egodocuments, one can feel the deposition of K. Barėnas’s personality.